Let’s talk about doctoral education. A reflection regarding the changes on it - Coutinho, Isabel Ribau (Advances in Social Sciences Research Journal, 2021)
Doctoral education is the link between research and higher education, being a hybrid area. In this context, the doctoral research project must correspond to the demands of both areas. The PhD. supervisor must be a team leader and, at some time, a doctorate guide, and a teacher. The PhD students must learn how to be a part of the research team, and simultaneously develop their research skills and knowledge. But PhD continues to be an individual and solitary journey, being the justification for it, the originality of knowledge created during the PhD. In the last years, in Portugal, PhD students and PhD supervisors were auscultated. The supervisors’ rules were captured, doctorate experiences were collected, and supervision processes were analysed and deepened knowledge about doctoral education. But still, this vision is incomplete not only because few supervisors took part in the research (first because the sample population were limited to one Portuguese University (NOVA Lisbon University) and secondly, because most of the PhD supervisors didn´t respond to the surveys. The data presented in this paper is part of a larger study that started at UNL before the pandemic. It examines the supervisor’s opinion regarding the PhD curriculum, constraints faced in day-to-day supervisor life, changes that may improve doctoral education (completion rates, decrease in attrition, curriculum, team supervision). But he also captures the doctorate perceptions regarding the doctoral research monitorization activities and instruments, constraints, and positive aspects during the PhD journey and, changes to be made in the PhD curriculum.